Asuhan Keperawatan Pada Klien Dengan Benigna Prostat Hiperplasia Post Open Prostatectomy Hari Ke-1 Di Ruang Gladiol Atas RSUD Sukoharjo - Arifin, Ryan Bastoni; , Okti Sri Purwanti, S.Kep., M.Kep., Ns., Sp.Kep.M.B (2015)
Background: Benign prostatic hyperplasia is the enlargement of the prostate gland which is commonly found in men over 50 years. One of the management of BPH client is surgery that on the lower abdomen to remove prostate tissue who have an enlarged prostate. Purpose : To determine the nursing care to clients with benign prostatic hyperplasia post open prostatectomi include assessment, intervention, implementation, and evaluation of nursing. Results: after already done the Askep during 3x24 hours, get reduced pain results from scale 6 to 3 , client mobility is advance, there are no sign of deficiency of fluid volume and there also infection of sufferer . Conclusion: Nursing care which is did during 3x24 get the result 3 problem solving partly and 1 problem solved.